Analysis of the pseudorandom number generators by the metrological characteristics - Мартинюк, Ганна Вадимівна; Оникієнко, Юрій Юрійович; Щербак, Леонід Миколайович (Eastern-European Journal of Enterprise Technologies, 2016)
The paper considers the method of checking the statistical conformity of the characteristics of realizations of noise signals with characteristics of uniform distribution law. The degree of conformity of realizations obtained from pseudorandom number sequence generators was checked by metrological characteristics. The conclusion on the generator usefulness was based on Pareto-optimal solutions for a multi-objective problem. The pilot study was conducted in the Matlab environment. The Martin method, congruent method and environment built-in generator were used as the pseudorandom number sequence generators. The research results showed that when using the Pareto-optimal solutions for the multi-objective problem of statistical conformity of metrological characteristics of realizations of white noise with the uniform distribution law for small volume samples (up to 5000 items), the generator built in the Matlab environment (function unifrnd) has a higher degree of conformity of realizations. However, when using the realizations of the white noise of larger volume (over 5000 items), the congruent method for pseudorandom number sequence generation becomes more significant. The Martin method has not proved as the best by the metrological characteristics for any sample volume.